An experimental platform using human intestinal epithelial cell lines to differentiate between hazardous and non-hazardous proteins. (June 2016) - Hurley, Bryan P.; Pirzai, Waheed; Eaton, Alex D.; Harper, Marc; Roper, Jason; Zimmermann, Cindi; Ladics, Gregory S.; Layton, Raymond J.; Delaney, Bryan
Abstract: Human intestinal epithelial cell lines (T84, Caco-2, and HCT-8) grown on permeable Transwell™ filters serve as models of the gastrointestinal barrier. In this study, this in vitro model system was evaluated for effectiveness at distinguishing between hazardous and non-hazardous proteins. Indicators of cytotoxicity (LDH release, MTT conversion), monolayer barrier integrity ([ 3 H]-inulin flux, horseradish peroxidase flux, trans-epithelial electrical resistance [TEER]), and inflammation (IL-8, IL-6 release) were monitored following exposure to hazardous or non-hazardous proteins. The hazardous proteins examined include streptolysin O (from Streptococcus pyogenes ), Clostridium difficile Toxins A and B, heat-labile toxin from enterotoxigenic Escherichia coli, listeriolysin O (from Listeria monocytogenes ), melittin (from bee venom), and mastoparan (from wasp venom). Non-hazardous proteins included bovine and porcine serum albumin, bovine fibronectin, and ribulose bisphosphate carboxylase/oxygenase (RuBisco) from spinach. Food allergenic proteins bovine milk β-lactoglobulin and peanut Ara h 2 were also tested as was the anti-nutritive food protein wheat germ agglutinin. Results demonstrated that this model system effectively distinguished between hazardous and non-hazardous proteins through combined analysis of multiple cells lines and assays. This experimental strategy may represent a useful adjunct to multi-component analysis of proteins with unknown hazard profiles. Highlights: Human intestinal epithelial cell lines grown on Transwell™ filters are an in vitro model of the gastrointestinal barrier. Cell lines responded differently when exposed to known hazardous or non-hazardous proteins. Indicators of monolayer barrier integrity were the most sensitive variabless. This platform may represent a useful adjunct to multi-component analysis of proteins with unknown hazard profiles.